Introduction of Computational Thinking Models in the Kurikulum Merdeka Through Scratch Games for Teachers at Gaussian Kamil School Semarang: Pengenalan Model Computational Thinking Pada Kurikulum Merdeka Melalui Scratch Game Untuk Guru Di Gaussian Kamil School Semarang - Muljono; Wise Herowati; Novianto Nur Hidayat; Harun Al Azies (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Efforts to increase understanding of Computational Thinking (CT) in the context of the Independent Curriculum in Indonesia with a focus on strengthening fundamental educational competencies, are carried out by utilizing the Scratch Game learning method. Gaussian Kamil School (GKS) faces the challenge of integrating CT skills in the Merdeka Curriculum, and teachers at GKS undergo training with Unplugged Programming Activities. The use of the Scratch Game with the Bee Bot Robot and the Activity Map board is an innovative solution. This service tests the development of CT skills through algorithm learning, especially through the Scratch Game. The results demonstrated an engaging learning experience and a better understanding of algorithm concepts. The Scratch Game themes prove the effectiveness of this method, especially for students who are not yet familiar with digital technology. This dedication also provides the foundation for a comprehensive Scratch Game module in teaching the algorithmic aspects of CT skills. The final recommendations include expanding the application of the Scratch Game in the teaching of CT algorithms in schools with limited access to technology, while supporting the development of modules that can be widely adopted to improve students' CT skills.